1969
DOI: 10.2307/3895931
|View full text |Cite
|
Sign up to set email alerts
|

Forage Production on a Clay Upland Range Site in Western Kansas

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Our work continues the tradition of applying statistical techniques to long-term data sets to characterize relationships between climate and primary production (e.g., Hulett and Tomanek 1969, Le Houerou et al 1988, Laurenroth and Sala 1992, Craine et al 2012, Sala et al 2012. Like previous studies, we use simple statistical models to explain historical variation in ANPP as a function of historical variation in precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Our work continues the tradition of applying statistical techniques to long-term data sets to characterize relationships between climate and primary production (e.g., Hulett and Tomanek 1969, Le Houerou et al 1988, Laurenroth and Sala 1992, Craine et al 2012, Sala et al 2012. Like previous studies, we use simple statistical models to explain historical variation in ANPP as a function of historical variation in precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…For individual sites, there are several possibilities. Seasonal precipitation may better predict production than annual precipitation (Hulett & Tomanek 1969; Shiflet & Dietz 1974; Smoliak 1986), there may be a carry‐over effect of production on that of the succeeding year (Hanson et al . 1982) and production may be affected by fire (Briggs & Knapp 1995) or grazing (Milchunas & Lauenroth 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between precipitation and grass production has been investigated, with varying thoroughness, in several Western range types (Craddock and Forsling 1938, Clarke et al 1943, Smoliak 1956, Blaisdell 1958, Sneva and Hyder 1962, Dahl 1963, Currie and Peterson 1966, Hulett and Tomanek 1969. In the Southwest, Nelson (1934), on the Jornada Experimental Range in southern New Mexico, found that current summer rainfall correlated well (r = 0.833) with average height growth of black grama (Bouteloua eriopoda Torr.)…”
Section: Introductionmentioning
confidence: 99%